(untitled) (AL MUNAZHZHARAH, 2021)
This study aims to conduct in-depth research on the factors and impacts of early marriage in Rembang Village, Sananwetan District, Blitar City. The research approach used is qualitative. Data were collected from a natural setting as a direct data source. The source of the data in this study is the subject of the study, namely couples who are married at an age under the provisions in accordance with Law No. 16 of 2019 concerning marriages of citizens of the Republic of Indonesia. Couples who were used as subjects based on cluster sampling technique, namely choosing married couples with selected criteria based on the age of 5 couples in Rembang Village, Sananwetan District, Blitar City. The results of this study are divided into two parts, namely an explanation of the driving factors. The influencing factors consist of factors originating from the educational, economic, and parental aspects. While the impact that arises consists of stress, feelings of inferiority and social impact.